Extent of Using Social Media as a Marketing Strategy: Basis for Proposed Marketing in Grade 12 ABM Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The study shows how much influence social media has on ABM students in their businessmarketing strategies; it also consists of different opinions expressed from purposive sampling.This research was done by gathering information through a survey questionnaire withparticipants from Bestlink College of the Philippines in Quezon City.Based on the results of the study, marketing strategies in Students addressed the above-citedextent and helped the Grade 12 ABM Students to recognize and effectively use social mediaas a tool in terms of Customer Engagement- creating a bond with customers helps thecustomer feel a connection with the business. Marketing Cost. It helps businesses to trackmarketing costs easily. Attraction to a Bigger Audience- It helps businesses improve theirsearch engines. Competition helps businesses to find new concepts. Brand Loyalty helpsbusinesses to build relationships. Cost offers customers cost-effective products that help thebusiness gain more customers. Sales help businesses distinguish the number of newcustomers who bought per period. Management through proper advertising can help abusiness develop good management skills. Brand Awareness through search engines canhelp business owners publicize their products. Customer Service- Provides support to bothprospective and existing customers. Data Connections- Being aware of the customer'sinternet connection can make the business owners. Communication is one of the importantkeys of businesses. Scammers- Business owners should be aware of the problems faced bythe customers and their Businesses. Cyber Security- Business owners must also prioritize thesecurity of the software they are using. Product Shipments- Businesses must improve visibilitythroughout the shipping process. Social media can help a business person to engage with their customers and get feedbackabout their business. Business people can use social media in various ways to improve theirmarketing strategy, such as advertising and promotional giveaways. Researchers may helpfuture researchers by giving them information for potential improvement of social mediabenefits and impact on businesses, helping them to gain more customers, review feedback,and build customer loyalty.
Keywords: Business